EFFECT OF A CONVENTIONAL AND MODIFIED-COGNITIVE BEHAVIOURAL COUNSELLING TECHNIQUES ON AGGRESSIVE BEHAVIOUR AMONG PUPILS OF ALMAJIRI INTEGRATED SCHOOLS IN GOMBE METROPOLIS - Dauda, Adepoju and Gwani , M. A Gwani; Oluwasanumi , Adepoju; Abubakar Gwani, Muhammad (African Journal of Behavioural and Scale Development Research, 2023)
ABSTRACT This study sought to examine the effect of a modified-cognitive restructuring counselling technique on aggressive behaviouramong Almajiri school pupil in Gombe Metropolis. The study was guided by three null hypotheses and employed a quasi-experimental design. The study sample comprised 162 pupils’ randomly drawn from the 5,961 pupils of five Almajiri integrated school in Gombe metropolis. The Buss-Perry Aggressive Questionnaire (Hausa Version, translated by Dauda and Adepoju, 2021) was used in collecting data. The data were analysed using ANCOVA. The results indicate that CCBT and RCBT had significant effect in reducing aggressive behaviours among the Almajiri pupils and that the counselling intervention strategy was not sensitive to the age of Almajiris. The results further indicated that the Almajiris exposed to the counselling intervention strategy had significantly lowered level of aggressive behaviour in comparison to those not exposed to the counselling intervention and thus no significant differences in aggressive behaviour was ditected between Almajiris exposed to CCBT and RCBT although RCBT reduced aggressive behaviour more than CCBT. The study thus suggested that the use of these two counselling techniques be stimulated to combat aggressive behaviour among Almajiri pupils, especially RCTB which appeared to be more effective.